Let us suppose that $f, g:(A, B)\to \mathbb{R}$ are both continuous on $(A, B)$ and for $[a, b]\subset (A, B)$, suppose that $g$ is of bounded variation on $[a, b]$ (we may add, if necessary, that also $f$ is of bounded variation).

The question is if it is true that $$\lim_{h\to 0, h\not=0}(R)\int_{a}^{b}f(x)\frac{g(x+h)-g(x)}{h}d x = (RS)\int_{a}^{b}f(x)d g(x) \, \, \, ?$$ If, for example, $g$ has a continuous derivative on $[a, b]$, then this is true , because we can pass to limit under the integral sign and the Riemann-Stieltjes integral is exactly $(R)\int_{a}^{b}f(x)g^{\prime}(x)dx=(RS)\int_{a}^{b}f(x)d g(x)$.

But I don't know what happens if $g$ is an arbitrary function of bounded variation.

There are counterexamples to this question ?

Thank you very much in advance.



The answer is yes, but we need to assume here that $g$ be of bounded variation on $(A,B)$ (or on some other open neighborhood of $[a,b]$), rather than just on $[a,b]$. On the other hand, we only need to assume that $g$ is continuous at $a$ and $b$, rather than on the entire interval $[a,b]$ -- if the integrals here with respect to $dg$ are understood in the more general Lebesgue--Stieltjes sense.

Indeed, take any $h\in(b-a)\wedge(B-b)$. Let $g_+(x):=g(x+)$ for $x\in(A,B)$, so that $g_+$ is the right-continuous regularization of $g$. Then $g$ differs from $g_+$ only on a countable set of points, and so, the integral $\int_a^bf(x)\frac{g(x+h)-g(x)}h\,dx$ will not change if we replace there $g$ by $g_+$. So, without loss of generality $g=g_+$ and hence $g(x+h)-g(x)=\int_{(x,x+h]}dg(u)$ for all $x\in[a,b]$.

Hence, in view of the Fubini theorem, \begin{equation} \int_a^b f(x)[g(x+h)-g(x)]\,dx=\int_a^b f(x)\,dx\,\int_{(x,x+h]}dg(u)=I_1+I_{21}-I_{22}+I_3, \end{equation} where \begin{align} I_1&:=\int_{(a,a+h]}dg(u)\,\int_a^u f(x)\,dx = \int_{(a,a+h]}dg(u)\,O(h)=o(h), \\ I_{21}&:=\int_{(a,b]} dg(u)\,\int_{u-h}^u f(x)\,dx = \int_{(a,b]} dg(u)\,[hf(u)+o(h)] =h\int_{(a,b]} dg(u)\,f(u)+o(h), \\ I_{22}&:=\int_{(a,a+h]} dg(u)\,\int_{u-h}^u f(x)\,dx = \int_{(a,a+h]} dg(u)\,O(h) =o(h), \\ I_3&:=\int_{(b,b+h]} dg(u)\,\int_{u-h}^b f(x)\,dx = \int_{(b,b+h]} dg(u)\,O(h) =o(h); \end{align} here we used the following: (i) $f$ is continuous on $(A,B)$ and hence bounded and uniformly continuous on some neighborhood of $[a,b]$ and (ii) $\int_{(c,c+h]}dg(u)=o(1)$ as $h\downarrow 0$, for each $c\in(A,B)$. It follows that \begin{equation} \lim_{h\downarrow 0}\int_a^bf(x)\frac{g(x+h)-g(x)}h\,dx = \int_{(a,b]} dg(u)\,f(u). \end{equation} E.g., if $g=1_{[b,B)}$ or $g=1_{(b,B)}$, then \begin{equation} \lim_{h\downarrow 0}\int_a^bf(x)\frac{g(x+h)-g(x)}h\,dx = \lim_{h\downarrow 0}\int_{b-h}^bf(x)\frac1h\,dx =f(b)= \int_{(a,b]} dg(u)\,f(u). \end{equation}

Similarly (or just by using the reflection $x\mapsto-x$), we have \begin{equation} \lim_{h\uparrow 0}\int_a^bf(x)\frac{g(x+h)-g(x)}h\,dx = \int_{[a,b)} dg(u)\,f(u). \end{equation}

So, if $g(a+)=g(a-)$ and $g(b+)=g(b-)$ (that is, if $g$ is continuous at $a$ and $b$), then \begin{align*} \lim_{h\to0}\int_a^bf(x)\frac{g(x+h)-g(x)}h\,dx &= \int_{[a,b]} dg(u)\,f(u)= \int_{(a,b)} dg(u)\,f(u) \\ & =\int_{(a,b]} dg(u)\,f(u)=\int_{(a,b]} dg(u)\,f(u). \end{align*}

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.